Genotype by Environment Interaction of IPB New Plant Type Rice Lines in Three Irrigated Lowland Locations - Syaifullah Rahim; Willy Bayuardi Suwarno; Hajrial Aswidinnoor (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
One essential objective of rice breeding is to obtain high-yielding varieties. This study aimed to (1) determine the effect of genotype (G), environment (E), and genotype by environment (GÃ—E) interaction on agronomic traits and yield of 12 lowland rice genotypes, (2) estimate variance components and repeatability (3) identify promising rice genotypes with good agronomic performance and high yield potential. The trials were conducted in three irrigated lowland locations from June to November 2020, using a randomized complete block design with three replications. The results showed that the GÃ—E interaction effect was significant on days to flowering, days to harvest, plant height, number of tillers, and panicle length. The genotype's main effect was significant on yield. Four IPB lines (IPB189-F-13-1-1, IPB189-F-23-2-2, IPB193-F-17-2-3, and IPB193-F-30-2-1) had a higher average yield than Ciherang and Inpari 32 varieties. The IPB189-F-23-2-2 had a panicle length stability across the three test locations and a higher average yield than the checks.